Insights from feature tracking of optical satellite data for studying rock glacier kinematics in the Northern Tien Shan - Wood, Ella; Bolch, Tobias; Streeter, Richard (Frontiers in Earth Science, 2025)
Rock glaciers are prevalent across the Tien Shan and exhibit complex, but poorly understood kinematics linked to climate and environmental fluctuations. This study employed a frequency domain cross-correlation method to investigate rock glacier velocities in the Northern Tien Shan. We compared different sources of satellite imagery, including 0.5m Pléiades, 3m Planet, 10m Sentinel-2 and 15m Landsat-8 data. Analysis of high-resolution Pléiades imagery in the Central Ile Alatau showed considerable spatial heterogeneity in flow. The highest median velocity of 0.65 m/yr was observed on Timofeyeva rock glacier, with an upper quartile value of 0.90 m/yr. Ordzhonikidze and Morennyi rock glaciers also exhibited high activity, with upper quartile values of 1.91 m/yr and 0.96 m/yr, respectively, despite considerably lower mean and median values than Timofeyeva. We observed bimodal velocity distributions on a number of rock glaciers, highlighting the limitations of using mean and median statistics for characterising rock glacier activity. Sentinel-2 data was capable of detecting kinematic patterns that closely reflected those identified by high-resolution Pléiades data. Velocities were derived from Sentinel-2 imagery for 672 rock glaciers across the Northern Tien Shan over a 7-year period (2016–2023). Many of the larger rock glaciers in the regional inventory exhibited active areas with velocities that exceeded 2 m per year. Topographic analysis in the Central Ile Alatau and visual inspection showed the fastest velocities to generally occur on lower, flatter areas near the rock glacier front. However, topography did not entirely explain the spatial flow heterogeneity. We interpret that these spatial patterns in activity are related to individual rock glacier’s internal structure.